Intractable Posterior Epistaxis due to a Spontaneous Low-Flow Carotid-Cavernous Sinus Fistula: A Case Report and a Review of the Literature. (29th December 2015) - Giotakis, A.; Kral, F.; Riechelmann, H.; Freund, M.
Abstract : We report a case of a 90-year-old patient with intractable posterior epistaxis presenting as the only symptom of a nontraumatic low-flow carotid-cavernous sinus fistula. Purpose of this case report is to introduce low-flow carotid-cavernous sinus fistula in the differential diagnosis of intractable posterior epistaxis. We provide a literature review for the sequence of actions for the confrontation of posterior epistaxis. We also emphasize the significance of the radiological diagnostic and therapeutic procedures in the management of posterior epistaxis due to pathology of the cavernous sinus. The gold-standard diagnostic procedure of carotid-cavernous sinus fistula is digital subtraction angiography (DSA). DSA with coils is also the state-of-the-art therapy. By failure of DSA, neurosurgery or stereotactic radiosurgery (SRS) may be used as alternatives. SRS may also be used as enhancement procedure of the DSA. Considering the prognosis of a successfully closed carotid-cavernous sinus fistula, recanalization occurs only in a minority of patients. Close follow-up is advised.